Model of Traditional Land Registration in Bali - IM Arjaya; I Made Suwitra; NK Arini Styawati; IK Kasta AW; NM Jayasenastri; I Ketut Alit Priana Nusantara (Law Doctoral Community Service Journal, 2023)
With the Decree of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 276/KEP-19.2/X/2017 Regarding the Appointment of Pakraman Village as the Subject of Joint Ownership Rights (Communal) Overland (the decree of the minister No. 276/KEP-19.2/X/2017) in the Province of Bali, Desa Pakraman/Desa Adat has been named as a customary law community. The discourse on strengthening the traditional village became relevant with the Bali Province Regional Regulation No. 4 of 2019 concerning Traditional Villages in Bali, which gave traditional villages legal standing as a legal subject. This research aims to determine how the model of customary land registration as communal ownership rights in Bali and the impact of land registration on the existence of land in Bali. Empirical research is used, and a legal approach, a conceptual approach, a case study approach, and a sociological approach are all used. Based on the research results, it was found that the customary land registration model of communal (or shared) ownership rights in Bali was registered as property rights using the minister's ATR/Ka decree as the legal basis. BPN No. 276/KEP-19.2/X/2017, so that the name of the right holder on the property rights certificate is the name of the traditional village. When customary land in Bali is registered as property rights, land registration makes it more likely that ownership rights can be moved.